Auditory Temporal Processing in Dancers. Issue 4 (August 2021) - Skoe, Erika; Scarpati, Erica V.; McVeety, Allison
While many studies have examined the auditory abilities of musicians, this study uniquely asks whether dance training, a similar yet understudied type of early-life training, also benefits auditory abilities. We focused this investigation on temporal resolution, given the importance of subtle temporal cues in synchronizing movement. We found that, compared to untrained controls, novice adult dancers who have trained continuously since childhood had enhanced temporal resolution, measured with a gap detection task. In an analysis involving current and former dancers, total years of training was a significant predictor of temporal resolution thresholds. The association between dance experience and improved auditory skills has implications for current theories of experience-dependent auditory plasticity and the design of sound-based educational and rehabilitation activities.